Economics and the family–match or mismatch? A review of Beckers "A Treatise on the Family" - Ben-Porath, Yoram (Journal of Economic Literature, 1982)
The author reviews and evaluates Beckers A Treatise on the Family which concerns (a) the allocation of roles and resources and distribution of income within families; (b) the formation dissolution growth and structure of families and (c) the implications of these analyses for inequality and social mobility. In the present paper Beckers approach and substantive conclusions regarding the role of theory and empirical evidence in the study of economics and the family are critically examined. It is suggested that while Beckers discussion is a source of many useful insights the theory does not attempt a systematic treatment of the transition from traditional to modern types of family. (EXCERPT)